The SNP rs460089 in the gene promoter of the drug transporter OCTN1 has prognostic value for treatment-free remission in chronic myeloid leukemia patients treated with imatinib: article - Machova Polakova, Katerina; Albeer, Ali; Polivkova, Vaclava; Krutska, Monika; Vlcanova, Katerina; Curik, Nikola; Fabarius, Alice; Klamova, Hana; Spiess, Birgit; Waller, Cornelius; Brümmendorf, Tim Henrik; Dengler, Jolanta; et al. (Leukemia, 2024)
Membrane transporters are important determinants of drug bioavailability. Their expression and activity affect the intracellular drug concentration in leukemic cells impacting response to therapy. Pharmacogenomics represents genetic markers that reflect allele arrangement of genes encoding drug transporters associated with treatment response. In previous work, we identified SNP rs460089 located in the promotor of SLC22A4 gene encoding imatinib transporter OCTN1 as influential on response of patients with chronic myeloid leukemia treated with imatinib. Patients with rs460089-GC pharmacogenotype had significantly superior response to first-line imatinib treatment compared to patients with rs460089-GG. This study investigated whether pharmacogenotypes of rs460089 are associated with sustainability of treatment-free remission (TFR) in patients from the EUROpean Stop Kinase Inhibitor (EURO-SKI) trial. In the learning sample, 176 patients showed a significantly higher 6-month probability of molecular relapse free survival (MRFS) in patients with GC genotype (73%, 95% CI: 60-82%) compared to patients with GG (51%, 95% CI: 41-61%). Also over time, patients with GC genotype had significantly higher MRFS probabilities compared with patients with GG (HR: 0.474, 95% CI: 0.280-0.802, p = 0.0054). Both results were validated with data on 93 patients from the Polish STOP imatinib study. In multiple regression models, in addition to the investigated genotype, duration of TKI therapy (EURO-SKI trial) and duration of deep molecular response (Polish study) were identified as independent prognostic factors. The SNP rs460089 was found as an independent predictor of TFR.
Online veröffentlicht: 21. Dezember 2023
Gesehen am 13.02.2024